Direct numerical simulation study of hydrogen/air auto-ignition in turbulent mixing layer at elevated pressures. (15th September 2018) - Yao, Tong; Yang, Wen Hao; Luo, Kai Hong
Highlights: DNS of H2-air mixing layer auto-ignition is performed under pressures 1–30 atm. At high pressures, HO2 can be used as an indicator for locating ignition spots. At high pressures, scalar dissipation has little influence on radical explosion. Abstract: Auto-ignition of turbulent stratified mixing layer between hydrogen and hot air under elevated pressures p = 1–30 atm is studied using direct numerical simulations (DNS) in this work. Homogeneous isotropic turbulence is superimposed on the field. Detailed chemical mechanism and multicomponent diffusion model are employed. Other than turbulent mixing ignition (TMI), homogeneous mixing ignition (HMI) and laminar mixing ignition (LMI) are also investigated for comparison. For both laminar and turbulent cases, the onset of auto-ignition always happens at the same most reactive mixture fraction isosurfaces. Most reactive mixture fractions in diffusion auto-ignition are inconsistent with HMI calculations and shift to the rich side owing to diffusion for all pressures. At elevated pressures, auto-ignition chemistry is different from low pressures. The importance of H2 O2 and HO2 is highlighted as radical sinks during the ignition process, and can also be used as an indicator for locating the ignition spots. Moreover, OH radicals can be used as a marker variable for the transition of auto-ignition to flame propagation under high pressures. Two stages are involved in the diffusion ignition process: radical explosion and thermal runaway. According to our study, under elevated pressures, turbulence has little influence on the radical explosion stage. The role of turbulence is to accelerate the thermal runaway stage in the kernels to make the ignition delay time (IDT) shorter than laminar cases.